IMPLEMENTASI METODE JIBRIL DALAM PEMBELAJARAN ILMU TAJWID DI BLOK C2 PUTRI PONDOK PESANTREN TAHFIDZUL QUR’AN AL-ASY’ARIYYAH KALIBEBER WONOSOBO - Permatasari, Putri; Shidiq, Ngarifin; Agus Faisal, Vava Imam (DAS Institute, 2023)
This study aims to 1) find out the application of the Jibril method in learning tajweed in Block C2 Putri Pondok Pesantren Tahfidzul Qur’an Al-Asy’ariyyah Kalibeber Wonosobo, 2)know the impact of the application of the Jibril method in learning tajweed in Block C2 Putri Pondok Pesantren Tahfidzul Qur’an Al-Asy’ariyyah Kalibeber Wonosobo, 3)know the supporting and inhibiting factors of the application of the Jibril method in learning tajweed in Block C2 Putri Pondok Pesantren Tahfidzul Qur’an Al-Asy’ariyyah. This research uses qualitative research in the form of field research. By using primary data sources directly through books, journals, and so on and secondary data i.e. indirect sources through observation, interviews, and documentation. So the data collection technique is carried out in accordance with the search for materials related to research, then followed by specific data. The data analysis uses data reduction, data presentation, and then drawing conclusions. The result showed that the Jibril method is the right method to be applied in learning tajweed. This method teaches students to read the Qur’an tartil and fluently. The steps of the Jibril method are first that the teacher first reads the reading that will be imitated by the students, then the students imitate the reading that has been read by the teacher.